Gambaran Gejala Depresi pada Mahasiswa Fakultas Kedokteran Universitas Mulawarman: Overview of Depression Symptoms in Medical Faculty Students, Mulawarman University - Nilna Nur Faizah; Sulistiawati Sulistiawati; Eka Yuni Nugrahayu; Jaya Mualimin; Arie Ibrahim (Jurnal Sains dan Kesehatan, 2021)
Abstract The prevalence of depressive symptoms among medical students is known to be higher because they have been faced with variety of stressors. The purpose of this study was to determine the depressive symptoms among undergraduate medical students of Mulawarman University. This was a quantitative descriptive research with univariate analysis. Beck Depression Inventory (BDI) was used to collect the primary data. A cross-sectional study was conducted on a total of 364 sampled students selected by purposive sampling technique. The obtained data were described using descriptive statistics. The results of this study showed that 177 students (48,6%) had low (minimal) levels of depression, 93 students (25,6%) had mild depression, 62 students (17,0%) had moderate depression, and 32 students (8,8%) had severe depression. In summary, most students in the Medical Study Program of Mulawarman University had minimal depressive symptoms. Abstrak Prevalensi gejala depresi pada mahasiswa kedokteran diketahui lebih tinggi karena mereka dihadapkan dengan stresor yang bervariasi. Tujuan penelitian ini yaitu untuk mengetahui gejala depresi pada mahasiswa kedokteran preklinik di Universitas Mulawarman. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan analisis univariat. Beck Depression Inventory (BDI) digunakan untuk mengumpulkan data primer. Studi potong lintang dilakukan pada 364 mahasiswa menggunakan teknik purposive sampling. Data yang telah diperoleh dideskripsikan menggunakan statistik deskriptif. Hasil penelitian menunjukkan sebanyak 177 (48,6%) mahasiswa memiliki tingkat depresi rendah (minimal), 93 mahasiswa (25,6%) memiliki gejala depresi ringan, 62 mahasiswa (17,0%) memiliki gejala depresi sedang, dan 32 mahasiswa (8,8%) memiliki gejala depresi berat. Sebagai kesimpulan, sebagian besar mahasiswa kedokteran Universitas Mulawarman memiliki gejala depresi minimal.